Adrenal function testing in dialysis patients – a review of the literature - Lara Brotzer (BMC, 2021)
Abstract Background Secondary adrenal insufficiency is a frequent issue in patients with renal replacement therapy. There are concerns about metabolism and clearance for adrenocorticotropic hormone (ACTH) and cortisol in addition to hemoconcentration as confounding factors during hemodialysis (HD). Therefore, ACTH testing is currently performed before or in between HD sessions. This review of the literature aims to evaluate the current evidence for validity of testing for adrenal insufficiency in patients on chronic renal replacement therapy. Methods A literature search of PubMed database for interventional and observational clinical trials was performed. Case reports and reviews were excluded. The search included all articles published until July 2020. Results Of 218 potentially eligible articles, 16 studies involving 381 participants were included. Seven studies performed an ACTH test before HD or in between HD sessions. There was no data available regarding ACTH testing during HD. But there was evidence of decreased cortisol levels during HD as compared to afterwards. All included 16 studies measured basal cortisol, and seven studies performed an ACTH test. Seven trials had comparable data of baseline cortisol for a quantitative analysis. Standardized mean difference of overall cortisol was 0.18 nmol/l (95%CI − 0.08 to 0.44) in the case group. Conclusions In patients undergoing renal replacement therapy, basal serum cortisol values are comparable to healthy volunteers. There is limited data on the validity of stimulated cortisol in these patients, especially during HD. Trial registration Registration no. CRD42020199245 .